Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Review: 62

Answer

$ab^{3}$

Work Step by Step

$\frac{\sqrt[4] (a^{6}b^{13})}{\sqrt[4] (a^{2}b)}=\sqrt[4] \frac{(a^{6}b^{13})}{(a^{2}b)}=\sqrt (a^{4}b^{12})=\sqrt[4] (a^{4})\times\sqrt[4] (b^{12})=ab^{3}$ We know that $\sqrt[4] (a^{4})=a$, because $(a)^{4}=a^{4}$. We also know that $\sqrt[4] (b^{12})=b^{3}$, because $(b^{3})^{4}=b^{3\times4}=b^{12}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.